2016
DOI: 10.1261/rna.053272.115
|View full text |Cite
|
Sign up to set email alerts
|

The local expression and trafficking of tyrosine hydroxylase mRNA in the axons of sympathetic neurons

Abstract: Synthesis and regulation of catecholamine neurotransmitters in the central nervous system are implicated in the pathogenesis of a number of neuropsychiatric disorders. To identify factors that regulate the presynaptic synthesis of catecholamines, we tested the hypothesis that the rate-limiting enzyme of the catecholamine biosynthetic pathway, tyrosine hydroxylase (TH), is locally synthesized in axons and presynaptic nerve terminals of noradrenergic neurons. To isolate pure axonal mRNA and protein, rat superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 34 publications
4
43
2
Order By: Relevance
“…Recent research suggested that tyrosine hydroxylase (TH) mRNA is localized to axons of sympathetic neurons, and demonstrated that its local translation facilitates axonal dopamine (DA) synthesis (Gervasi et al, 2016). The finding that TH mRNA is present in axons of primary sympathetic neurons is consistent with the detection of TH mRNA in brain regions innervated by catecholaminergic terminals (Lewis et al, 1991; Melia et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggested that tyrosine hydroxylase (TH) mRNA is localized to axons of sympathetic neurons, and demonstrated that its local translation facilitates axonal dopamine (DA) synthesis (Gervasi et al, 2016). The finding that TH mRNA is present in axons of primary sympathetic neurons is consistent with the detection of TH mRNA in brain regions innervated by catecholaminergic terminals (Lewis et al, 1991; Melia et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Ang II influences sympathetic transmission by enhancing NE synthesis, facilitating NE release and inhibiting NE uptake (Reid 1992). Previously, it was demonstrated that TH mRNA is trafficked to the distal axons of primary SCG neurons, directed by a cis-acting zipcode located in the 3'UTR of the transcript, and is locally translated (Gervasi et al 2016). The present study demonstrates that treatment of SCG neurons with a selective Ang II agonist increases the axonal levels of TH and DBH mRNA and results in elevated presynaptic NE synthesis and release in primary rat sympathetic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we identified a putative 50-nucleotide zipcode in the 3 0 untranslated region of the TH mRNA that was necessary and sufficient for the axonal localization of the message in primary SCG neurons (Gervasi et al 2016). However, little is known about the proteins and possibly other mRNAs that associate with TH-zipcode and regulate the axonal trafficking and local translation of the TH message.…”
Section: Th Zipcode Rnp Complexes Contain Dbh Mrna and Proteins Involmentioning
confidence: 99%
“…Axonal β-catenin mRNA concentrates in the presynaptic terminals of CNS neurons in culture, where its translation product regulates synaptic vesicle release during synaptogenesis (Taylor and others 2013). Tyrosine hydroxylase mRNA, which encodes the rate-limiting enzyme in catecholamine biosynthesis, localizes to sympathetic axons to presumably regulate neurotransmitter synthesis (Gervasi and others 2016a). Axonal translation of mRNAs for the nuclear-encoded mitochondrial proteins, COXIV and ATP5G1 , key components of the oxidative phosphorylation chain, regulate axonal mitochondrial ATP production to support sympathetic axon survival (Aschrafi and others 2010; Aschrafi and others 2008; Gioio and others 2001; Gioio and others 2004; Natera-Naranjo and others 2012; Wen and others 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These localization motifs can be defined by their primary, secondary, or tertiary structures (Aschrafi and others 2010; Bolognani and others 2010; Di Liegro and others 2014; Khvorova and Wolfson 2012; Li and others 2010). Although a number of axonal localization motifs have now been uncovered, these have not shown any consensus nucleotide sequence for axonal localization (Aronov and others 1999; Ben-Yaakov and others 2012; Cosker and others 2016; Cosker and others 2013; Gervasi and others 2016b; Kaplan and others 2009; Merianda and others 2015; Merianda and others 2013a; Vuppalanchi and others 2010; Wu and others 2005; Yoo and others 2013; Yoon and others 2012; Yudin and others 2008; Zhang and others 2001). It should be noted that most of the approaches looking for commonality between RNA motifs have been limited to asking if the motif is shared with other axonal mRNAs.…”
Section: Introductionmentioning
confidence: 99%